Problem of the dynamic topology architecture of rechargeable wireless sensor networks - Xu DING; Jiang-hong HAN; Lei SHI; Wei XIA; Zhen-chun WEI (Tongxin xuebao)
The time-varying dynamic topology model for rechargeable wireless sensor networks is proposed in accordance with the scenario that the wireless charging equipment plays the role of a data collector while charging sensor nodes at the meantime.An optimization problem aiming to maximize the vacation time ratio of the wireless charging equipment is then raised from the study of the model established.Through comprehensively analyzing of the working states and constraints of different sensor nodes as well as the wireless charging equipment during different time instances,the multi-phase linear programming problem with the identical optimality is then obtained.The optimal dynamic data routing schemes of different phases compatible with the dynamic topology architecture are acquired from solving this optimization problem.What is more,the working strategies of the wireless charging/data collecting equipment are also obtained,simultaneously.Compared with the results of the previous work,the objective values are increased by no less than 20%.